Usability and User Experience of Environmental Control Units: Temporal Stress and Control Modalities’ Effects On Performance Measures and Cognitive and Affective States - Takahashi, Brandon K.; Hancock, Gabriella M. (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Environmental control units (ECUs) are an integral assistive product for individuals who suffer from spinal cord injuries (SCIs). One noteworthy SCI population to study is veterans due to the exponential increase in SCI injuries amongst them over the past 50+ years. Assistive technology is intended to improve a person’s well-being, independence, and mobility, but if it is rendered ineffective and unusable for these goals, then it can do more harm than good. However, research on ECUs focuses on technology acceptance or identification of opportunities and costs when it comes to the devices resulting in a lack of usability testing to improve their design and functioning. A study conducted on the control modalities (touchscreen vs. voice control) that manipulate navigation through the ECU’s interface, and a time pressure stressor (high vs. low) examined the usability and user experience of this device can identify areas of improvement for designers. Both performance and self-reports of operators’ cognitive affect states were evaluated in this study. Recommendations to improve the device’s design to support those with mobility limitations are herein discussed.